Proposição de Mecanismos de Acompanhamento e Controle de Projetos Executados com o Apoio de uma Fundação de Apoio: Estudo de Caso da Universidade Federal de Mato Grosso do Sul - Silva, Fabiana Fernandes Moreira da (2021)
The support foundations for higher education institutions are private institutions, created with the purpose of supporting projects of interest to Federal Institutions of Higher Education and Scientific and Technological Institutions, including the administrative and financial management necessary for the execution of projects. The Federal Constitution of Brazil states that the powers must maintain, in an integrated manner, internal control systems, with the purpose of proving the legality and evaluating the results of the application of public resources by private law entities. In this sense, this research aimed to analyze the efficiency of the monitoring and control mechanisms, carried out by the Federal University of Mato Grosso do Sul – UFMS, of the legal instruments signed with an accredited support foundation. As for the methodological procedures, the exploratory, descriptive and applied research had a qualitative approach, using the case study design. Data were collected from document analysis, by conducting a focus group and by inductive logic, through observation and experience of the researcher. Data processing was based on the technique of content analysis. The legal requirements and guidelines of the external control bodies were identified, as well as the practices adopted by the University for the monitoring and control of the legal instruments entered into by it with a supporting foundation. It was concluded that the policy adopted by UFMS can be improved, thus, additional elements were identified to compose the monitoring and control mechanisms, which were recommended in this work. Keywords: Supporting foundations. Federal institutions of higher education. Internal control.